The social environment and walking behavior among low-income housing residents - Caspi, Caitlin E.; Kawachi, Ichiro; Subramanian, S.V.; Tucker-Seeley, Reginald; Sorensen, Glorian (Social science & medicine (1982), 2013)
Walking, both for leisure and for travel/errands, counts toward meeting physical activity recommendations. Both social and physical neighborhood environmental features may encourage or inhibit walking. This study examined social capital, perceived safety, and disorder in relation to walking behavior among a population of low-income housing residents. Social and physical disorder were assessed by systematic social observation in the area surrounding 20 low-income housing sites in greater Boston. A cross-sectional survey of 828 residents of these housing sites provided data on walking behavior, socio-demographics, and individual-level social capital and perceived safety of the areas in and around the housing site. Community social capital and safety were calculated by aggregating individual scores to the level of the housing site. Generalized estimating equations were used to estimate prevalence rate ratios for walking less than 10 min per day for a) travel/errands, b) leisure and c) both travel/errands and leisure. 21.8% of participants walked for travel/errands less than 10 min per day, 34.8% for leisure, and 16.8% for both kinds of walking. In fully adjusted models, those who reported low individual-level social capital and safety also reported less overall walking and less walking for travel/errands. Unexpectedly, those who reported low social disorder also reported less walking for leisure, and those who reported high community social capital also walked less for all outcomes. Physical disorder and community safety were not associated with walking behavior. For low-income housing residents, neighborhood social environmental variables are unlikely the most important factors in determining walking behavior. Researchers should carefully weigh the respective limitations of subjective and objective measures of the social environment when linking them to health outcomes. ► Low individual social capital and safety at the housing site were modestly associated with less walking. ► Low social disorder was unexpectedly associated with less walking. ► High community social capital was associated with less walking, in contrast to individual social capital. ► Social environmental variables at low-income housing sites are unlikely the most important factors in determining walking behavior.